2022
DOI: 10.1371/journal.pone.0261976
|View full text |Cite
|
Sign up to set email alerts
|

Expected global suitability of coffee, cashew and avocado due to climate change

Abstract: Coffee, cashew and avocado are of high socio-economic importance in many tropical smallholder farming systems around the globe. As plantation crops with a long lifespan, their cultivation requires long-term planning. The evaluation of climate change impacts on their biophysical suitability is therefore essential for developing adaptation measures and selecting appropriate varieties or crops. In this study, we modelled the current and future suitability of coffee arabica, cashew and avocado on a global scale ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 35 publications
0
31
0
4
Order By: Relevance
“…Prioritizing a rich diversity of NUS over staple crops such as wheat, maize, and rice will lead to healthier diets and improved nutrition and contribute to sustainable development [59]. In addition, a recent study on plantation crops such as coffee, cashew and avocado that similarly have a long lifespan found shifts in suitable growing regions due to climate change for all investigated crops [60]. For both cashew and avocado, areas suitable for cultivation are expected to expand globally.…”
Section: Discussionmentioning
confidence: 99%
“…Prioritizing a rich diversity of NUS over staple crops such as wheat, maize, and rice will lead to healthier diets and improved nutrition and contribute to sustainable development [59]. In addition, a recent study on plantation crops such as coffee, cashew and avocado that similarly have a long lifespan found shifts in suitable growing regions due to climate change for all investigated crops [60]. For both cashew and avocado, areas suitable for cultivation are expected to expand globally.…”
Section: Discussionmentioning
confidence: 99%
“…also confirms that crops in Senegal, South-West Mali, Burkina Faso, and South-West Niger are more responsive to climate stresses and impact negatively on crop production in the four regions. The study byBagbohouna et al (2020) revealed that an increase in maximum temperature (Tmax) and a variation in minimum temperature (Tmin) have a negative impact on crop yields Grüter et al (2022). confirm that climate change in the form of high temperatures and flooding impedes the growth of coffee, cashew, and avocado in Guinea Bissau.…”
mentioning
confidence: 84%
“…Climate constraints in Nigeria are dominated by high temperatures (Haider, 2019). Due to climate change and the expansion of coffee cultivation to marginal lands, such as in Nigeria's north, these constraints are expected to grow in importance in several coffeegrowing regions (Grüter et al, 2022;Pereira, 2017). Poor weather and a lack of water are limiting coffee production.…”
Section: Literature Reviewmentioning
confidence: 99%